How does sociocultural identity influence Indonesian students’ intention to study in Malaysia? - Hendriana, Evelyn; Awang, Khairil Wahidin; Raja Yusof, Raja Nerina; Bojei, Jamil (Universiti Teknologi MARA Malaysia, 2019)
The growing number of international students worldwide stimulates the need to understand the factors influencing students’ decision-making process. This study aims to examine the influence of sociocultural identification on students’ intention to study in Malaysia by applying social identity theory. It also tests the mediation effect of destination and institution images in the relationship between sociocultural identification and students’ intention. Due to the tendency of individuals to maintain self-congruity in making tourism decision, this research will contribute to the tourism literature by providing insights on the effect of national identity, consumer cosmopolitanism, and consumer ethnocentrism on education tourism decision. This research applied the multistage cluster sampling technique by collecting data from senior high school students in eight provinces in Indonesia. From more than 1,000 questionnaires distributed, 888 responses could be used in the analysis. Data were analysed using partial least square-structural equation modelling. This study found that national identity, consumer cosmopolitanism, and consumer ethnocentrism were interrelated. The results showed that national identity might affect students’ intention only through destination and institution images. On the other hand, consumer cosmopolitanism and consumer ethnocentrism had direct and indirect effects on students’ intention to study in Malaysia respectively.